2020
DOI: 10.1007/s13314-020-00385-w
|View full text |Cite
|
Sign up to set email alerts
|

First report of Fusarium concentricum causing fruit blotch on roselle (Hibiscus sabdariffa)

Abstract: Symptoms of fruit blotch were noticed on roselle (Hibiscus sabdariffa) in Relau, Penang and Karangan, Kedah. The aims of this study were to isolate and identify the suspected causal pathogen and to evaluate its pathogenicity towards the host. Two isolates of Fusarium sp. were isolated from the blotched fruits of H. sabdariffa and morphologically identified. Sequences analysis based on translation elongation factor (TEF1-α) and mitochondrial small subunit ribosomal DNA (mtSSU rDNA) showed that both isolates had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Fusarium appeared as white or blackish-white and showed chlamydospores and macroconidia on PDA after seven days of culture. Huda-Shakirah et al (2020) found 3–5 long, thin walled, septate macroconidia on a F. concentricum fugal stain under microscopic observation, which supports our present findings. Zhu et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fusarium appeared as white or blackish-white and showed chlamydospores and macroconidia on PDA after seven days of culture. Huda-Shakirah et al (2020) found 3–5 long, thin walled, septate macroconidia on a F. concentricum fugal stain under microscopic observation, which supports our present findings. Zhu et al .…”
Section: Discussionsupporting
confidence: 92%
“…Macroconidia were sporodochia and fusiform. Huda-Shakirah et al (2020) found 3-5µm long, thin walled, septate macroconidia on a F. concentricum fugal stain under microscopic observation, which supports our present findings. Zhu et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The newly inflicted Fusarium spp. On D. officinale have been also found as plant pathogens and innocuous saprophytes, e.g., F. concentricum causing fruit blotch on Hibiscus sabdariffa, stem rot on Paris polyphylla, fruit rot on pepper and banana, leaf spot on mango, wilt on Podocarpus macrophyllus, and ear rot on maize, originally named by Nirenberg and O'Donnell [24,[29][30][31][32]. F. curvatum has been also described as a new taxon by Lombard et al [16], originally named F. oxysporum (matthiolae and meniscoideum formae speciales), which was regarded as a FOSC member.…”
Section: Discussionmentioning
confidence: 99%
“…F. concentricum has a wide host range, associating with multiple diseases on different hosts such as stem rot of Paris polyphylla var. chinensis and fruit rot of pepper and banana [54]. Fusarium fungi is a kind of important plant pathogenic fungi, widely distributed in nature [55].…”
Section: Ficus Hirta Figs Microbial Compositionmentioning
confidence: 99%